2019
DOI: 10.1002/iju5.12098
|View full text |Cite
|
Sign up to set email alerts
|

Renal cell carcinoma treatment during pregnancy: Histopathological findings suggestive of rapid tumor growth

Abstract: Introduction Diagnosis of renal cell carcinoma during pregnancy is rare. We report a case of renal cell carcinoma during pregnancy with rapid growth. Case presentation A 39‐year‐old woman presented to our hospital for treatment of renal tumor at 22 weeks gestation. The tumor had a cystic lesion with a partition and showed rapid growth from 28 mm to 32 mm over a period of 4 weeks. The tumor was diagnosed as renal cell carcinoma and an open partial nephrectomy was scheduled at 26 weeks gestation. The operation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…To rule out this possibility, a timely nephrectomy (partial or radical) should be performed to make a definite diagnosis. Ohyama et al presented a case of renal mass in pregnancy in which the diagnosis was confirmed preoperatively via fine-needle biopsy; however, one should remember that the negative results do not rule out malignancy [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To rule out this possibility, a timely nephrectomy (partial or radical) should be performed to make a definite diagnosis. Ohyama et al presented a case of renal mass in pregnancy in which the diagnosis was confirmed preoperatively via fine-needle biopsy; however, one should remember that the negative results do not rule out malignancy [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…RCC is the most common tumor in pregnancy and seems heterogeneous; each patient showed variable tumor size, manifestation, and growth rate [ 8 ]. A meta-analysis of 286 solid localized renal lesions revealed a mean growth rate of 0.28 cm each year (median 0.28, range 0.09 to 0.86) during a mean follow-up of 34 months (median 32, range 26 to 39) [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, according to the current SAGES (Society of American Gastrointestinal and Endoscopic Surgeons) guidelines for the use of laparoscopy during pregnancy [ 15 ], laparoscopic surgery, including renal procedures, may be performed during any trimester of pregnancy despite the possible risk of triggering uterine contractions, thus causing fetal distress or even spontaneous abortion due to surgical manipulation [ 18 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the current era of robot-assisted surgery, the partial nephrectomy techniques were revolutionized. This was followed by the robot-assisted experience with partial nephrectomy during pregnancy [ 18 20 ]. The retroperitoneoscopic approach to the kidney was first described by Gaur et al 1993.…”
Section: Introductionmentioning
confidence: 99%